Tomato leaf disease detection using convolutional neural network - Hasan, Md. Riazul; Hossain, Md. Shajib; Islam, Md. Minhajul; Rahman Apu, Md. Rejoanur; Moli, Farzana Akter (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.